4, 7-Didehydro-neophysalin B Protects Rat Lung Epithelial Cells against Hydrogen Peroxide-Induced Oxidative Damage through Nrf2-Mediated Signaling Pathway. (12th September 2022) - Zhong, Qiu; Sun, Yaogui; Khan, Ajab; Guo, Jianhua; Wang, Zhirui; Sun, Na; Li, Hongquan
Abstract : The administration of 4, 7-didehydro-neophysalin B is expected to be a promising strategy for mitigating oxidative stress in respiratory diseases. This study was aimed at investigating the efficacy of 4, 7-didehydro-neophysalin B for apoptosis resistance of rat lung epithelial cells (RLE-6TN) to oxidative stress and evaluating its underlying mechanism of action. The RLE-6TN cells treated with hydrogen peroxide (H2 O2 ) were divided into five groups, and 4, 7-didehydro-neophysalin B was administered into it. To evaluate its mechanism of action, the expression of oxidative stress and apoptotic proteins was investigated. 4, 7-Didehydro-neophysalin B significantly inhibited H2 O2 -induced RLE-6TN cell damage. It also activated the Nrf2 signaling pathway which was evident from the increased transcription of antioxidant responsive of KLF9, NQO1, Keap-1, and HO-1. Nrf2 was found to be a potential target of 4, 7-didehydro-neophysalin B. The protein levels of Bcl-2 and Bcl-xL were increased while Bax and p53 were decreased significantly. Flow cytometry showed that 4, 7-didehydro-neophysalin B protected RLE-6TN cells from apoptosis and has improved the oxidative damage. This study provided a promising evidence that 4, 7-didehydro-neophysalin B can be a therapeutic option for oxidative stress in respiratory diseases.